2021
DOI: 10.1101/2021.03.07.434274
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diet’s impact dictated by synonymous mitochondrial SNP interacting with nucleotype

Abstract: Animals vary genetically in responses to dietary change. Both mitochondrial and nuclear genomes contribute to this variation, but the role of combinatorial "mito-nuclear" genetic variation is understudied. We do not know whether specific nutrients modify patterns of mito-nuclear variation, nor whether putative epigenetic mechanisms play a role. Here, we show that enriching dietary essential amino acids or lipids modifies patterns of mito-nuclear variation in Drosophila life-history, including transgenerational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 147 publications
(272 reference statements)
0
2
0
Order By: Relevance
“…These studies include Zhu et al [10], where authors found mitonuclear interactions impacted ageing under caloric restriction, with certain mitonuclear genotypes being more impacted than others. More recently, Dobson et al [38] demonstrated that parental effects of dietary lipid and amino acid variation on offspring fitness is modulated by mitonuclear interactions. Furthermore, Aw et al [17] examined how mitonuclear interactions shaped metabolic flexibility to diet, with certain genetic combinations constraining metabolism on certain nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…These studies include Zhu et al [10], where authors found mitonuclear interactions impacted ageing under caloric restriction, with certain mitonuclear genotypes being more impacted than others. More recently, Dobson et al [38] demonstrated that parental effects of dietary lipid and amino acid variation on offspring fitness is modulated by mitonuclear interactions. Furthermore, Aw et al [17] examined how mitonuclear interactions shaped metabolic flexibility to diet, with certain genetic combinations constraining metabolism on certain nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…The number of offspring produced can be a function of lifespan, underpinning the quality of somatic tissue maintenance. Much research continues to focus on intergenerational effects of variations in nutritional supply and quality on offspring development and fitness [4,13,14]. Thus, we now appreciate that poor maternal conditions can limit offspring development through poor provisioning and care of eggs and juveniles [15].…”
Section: Introductionmentioning
confidence: 99%